Analisis Formulasi Shampo Antiketombe Pada Tanaman Herbal Belimbing Wuluh (Avveora Bilimbi) dan Daun Pandan Wangi (Pandanus Amaryllifolius Roxb.) dengan Metode Ekstraksi: Literature Review - Putri Nur Auliya Rahman; Indiarti Ayu Silvia; Getrudis Anita Seran; Firdha Senja Maelaningsih (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Dandruff is a common scalp problem affecting many people around the world. The use of chemicals in hair care products often raises concerns about side effects and long-term effects on hair and scalp health. Therefore, this review article aims to develop a natural-based anti-dandruff shampoo formulation using plant extracts such as starfruit (Averroa bilimbi) and fragrant pandan leaves (Pandanus amaryllifolius Roxb). Further analysis of the active compound content in the extract showed that there were bioactive components in pandan leaves, and ascorbic acid in starfruit which was proven to have antibacterial and antimicrobial properties as well as anti-dandruff properties. The purpose of this review article is to show that the use of herbal plants such as starfruit leaves and pandan wangi leaves in anti-dandruff shampoo formulations has great potential to provide a natural and effective solution in treating dandruff problems without causing side effects. adverse side effects. The practical implication of this research is to develop hair care products that are more environmentally friendly and focus on scalp health.